NLRP3 Inflammasome: The Stormy Link Between Obesity and COVID-19 - López-Reyes, Alberto; Martinez-Armenta, Carlos; Espinosa-Velázquez, Rocio; Vázquez-Cárdenas, Paola; Cruz-Ramos, Marlid; Palacios-Gonzalez, Berenice; Gomez-Quiroz, Luis Enrique; Martínez-Nava, Gabriela Angélica (Frontiers in Immunology, 2020)
Introduction: Several countries around the world have faced an important obesity challenge for the past four decades as the result of an obesogenic environment. This disease has a multifactorial origin and it is associated with multiple comorbidities including type 2 diabetes, hypertension, osteoarthritis, metabolic syndrome, cancer and dyslipidemia. With regards to dyslipidemia, hypertriglyceridemia is a well-known activator of the NLRP3 inflammasome, triggering adipokines and cytokines secretion which in addition induce a systemic inflammatory state that provides an adequate scenario for infections, particularly those mediated by viruses such as HIV, H1N1 influenza and SARS-CoV-2. The SARS-CoV-2 infection causes the coronavirus disease 2019 (COVID-19) and it is responsible for the pandemic that we are currently living. The COVID-19 causes an aggressive immune response known as cytokine release syndrome or cytokine storm that causes multiorgan failure and in most cases leads to death. In the present work, we aimed to review the molecular mechanisms by which obesity-associated systemic inflammation could cause a more severe clinical presentation of COVID-19. Conclusion: The SARS-CoV-2 infection could potentiate or accelerate the pre-existing systemic inflammatory state of individuals with obesity, via the NLRP3 inflammasome activation and the release of pro-inflammatory cytokines from cells trough Gasdermin-pores commonly found in cell death by pyroptosis.